2019
DOI: 10.3390/catal9121062
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Supported FeS/Fe3O4 Composite for Catalyzed Fenton-Type Degradation of Ciprofloxacin

Abstract: The Fenton-type oxidation catalyzed by iron minerals is a cost-efficient and environment-friendly technology for the degradation of organic pollutants in water, but their catalytic activity needs to be enhanced. In this work, a novel biochar-supported composite containing both iron sulfide and iron oxide was prepared, and used for catalytic degradation of the antibiotic ciprofloxacin through Fenton-type reactions. Dispersion of FeS/Fe 3 O 4 nanoparticles was observed with scanning electron microscopy-energy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…1 e and f, the FeS crystals exhibit a flaky morphology and are uniformly dispersed across the surface of the fly ash, with an average length ranging from 40 to 80 nm. This morphology bears a resemblance to the nano FeS synthesized by Wang et al 33 , thereby suggesting, in conjunction with SEM analysis, the efficacy of the ultrasonic precipitation method in loading nano FeS onto fly ash particles. The uniform distribution of nanocrystals on nFeS-F signifies that using fly ash as a carrier can notably enhance the dispersion and stability of nano-FeS, regulate particle size, and effectively mitigate nanoparticle agglomeration.…”
Section: Resultssupporting
confidence: 71%
“…1 e and f, the FeS crystals exhibit a flaky morphology and are uniformly dispersed across the surface of the fly ash, with an average length ranging from 40 to 80 nm. This morphology bears a resemblance to the nano FeS synthesized by Wang et al 33 , thereby suggesting, in conjunction with SEM analysis, the efficacy of the ultrasonic precipitation method in loading nano FeS onto fly ash particles. The uniform distribution of nanocrystals on nFeS-F signifies that using fly ash as a carrier can notably enhance the dispersion and stability of nano-FeS, regulate particle size, and effectively mitigate nanoparticle agglomeration.…”
Section: Resultssupporting
confidence: 71%
“…This indicated that the SFe bond broke during the reaction process and S element existed in a stable form like metal sulfate. The form changing of S element promoted the electron transfer between nFe 3 O 4 core and the solution, iron and iron at the interface, thereby promoting Fe 3+ /Fe 2+ cycle and the catalytic capacity of nFe 3 O 4 (Wang et al, 2019). HO• attacked the benzene ring of BTEX forming various intermediate phenols.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies demonstrate that iron sulphide (FeS) can be coupled with catalysts to address the unsatisfactory performance of Fe 3 O 4 catalyst which could encourage the production of OH for the breakdown of organic contaminants. 84,85 In a recent work, the honeycombshaped Fe 3 O 4 /FeS composite catalyst made from pollen exhibited phenol degradation efficiency of 95% at 5 minutes and 99% at 60 minutes. 86 The use of catalysts in plastic waste pyrolysis has considerably increased traction.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%